Teaching young people computational thinking using MIT App Inventor - Raddad, Faqihi (Kansas State University, 2019)
MIT App Inventor is a visual programming platform targeted at beginners to develop mobile apps for Android smart devices. It reduces limitations to programming and app development using a block-based language that decreases syntactic mistakes and encapsulates mobile device features into high-level abstractions that are straightforward to incorporate into apps. This study investigates how App Inventor can be integrated into high school computer science and engineering courses to foster computational thinking by developing mobile apps. Teaching fundamental computational thinking concepts and skills to high school students is currently a curricular concentration in various nations. Working in correspondence to this aim are advanced programming environments, curricula, and learning methodologies that intend to make computer science more convenient and motivating. In this study, we explain the design and evaluation of App Inventor, a programming language that aims to help novice programmers develop computational skills through building mobile applications. As observed in this study, App Inventor can be a convenient and powerful platform that could entirely support introductory level courses and foster computational thinking.
Keywords: Computational thinking; App inventor; Mobile applications; K-12; School